The Effect Of Administration Of Mecobalamin & Curcumin As Antioxidants In Nasopharynx Carcinoma Patients Post Cisplatin Regimen Chemotherapy With Hearing Impairment - Matea, Ari; Primadewi, Novi (Indonesian Basic and Experimental Health Sciences, 2024)
INTRODUCTION Nasopharyngeal carcinoma (NPC) is a common type of cancer in Southeast Asia, and its treatment often involves a cisplatin chemotherapy regimen. Ototoxicity is a side effect that often occurs in patients receiving this regimen. Antioxidant therapy, both synthetic and natural, such as curcumin, has been studied as having the potential to reduce ototoxicity due to cisplatin. This study was conducted to evaluate the effect of administering mecobalamin and curcumin as antioxidants in patients with nasopharyngeal carcinoma after cisplatin chemotherapy regimen with hearing loss. METHOD This study was an observational study with a cross sectional design, using consecutive sampling with inclusion criteria, namely patients diagnosed with NPC receiving the cisplastin regimen and willing to take part in the study. The data obtained was then analyzed using the Rank-Biserial Correlation's Test. Research approval was obtained from the Medical Research Ethics Commission, Faculty of Medicine, Sebelas Maret University/RSUD Dr. Moewardi Surakarta. RESULTS Of the 30 NPC patients who received cisplatin from the ENT-KL installation section of Dr Moewardi Hospital in the period March - September 2023, 30 data were obtained for each right ear and left ear. The average hearing threshold before intervention was 33.79 ± 10.40 dB and 34.10 ± 9.75 for the right and left ears. There was a difference in the average increase in hearing threshold for all parameters (Group I: Mecobalamin, Group II: Curcumin, Group III: Curcumin + Mecobalamin), with a value of p=0.000 (p<0.05). From these data it was concluded that the combined therapy of both was able to increase the hearing threshold along with the chemotherapy series. CONCLUSION Based on the research results, administration of mecobalamin and curcumin as antioxidants has a significant effect on patients with nasopharyngeal carcinoma after cisplatin chemotherapy regimen with hearing loss.